Breakup mode transformation of leaky dielectric droplet under direct current electric field. (November 2017) - Huang, Xin; He, Limin; Luo, Xiaoming; Yang, Donghai; Shi, Kaiyue; Yan, Haipeng
Highlights: The CLSVOF method is proposed to capture the motion of droplet interface. Change of breakup mode relies on the electric capillary number and viscosity ratio. Position of double symmetrical vortices affects the structure of droplet tip. Abstract: The breakup behavior of leaky dielectric droplet in the presence of direct current electric field is investigated by simultaneously solving the electric field equations and the full incompressible Navier-Stokes equations. The coupled Level Set and Volume of Fluid method is proposed to capture the motion of droplet interface. The present numerical method is validated and is well consistent with acceptable results in the literature. This paper mainly focuses on the effects of electric capillary number Ca and viscosity ratio λ on the mode transformation of droplet breakup. With increasing Ca, the droplet experiences the transformation from jet-like breakup to dumbbell-like breakup, while the increase of λ results in the shift from dumbbell-like breakup to jet-like breakup. The numerical experiments demonstrate that the mode transformation of droplet breakup depends on the evolutions of velocity field and pressure field.